P168 WHERE WILL FECAL MICROBIOTA TRANSPLANTATION FIT IN THE TREATMENT ALGORITHMS FOR CROHN'S DISEASE AND ULCERATIVE COLITIS: A SYNTHESIS OF COMPLETED, ONGOING AND FUTURE TRIALS. (18th January 2018) - Song, Yiran; Wang, Peiqi; Parian, Alyssa; Chen, Gongying; Dudley-Brown, Sharon; Li, Ge; Gao, Yidan; Zhang, Bingbing; Kalloo, Anthony; Hutfless, Susan
Abstract: Background: The United States Food and Drug Administration (FDA) exercises enforcement discretion for fecal microbiota transplantation (FMT) for Clostridium difficile infection not responsive to standard therapies. An investigational new drug (IND) is required for all other uses. Since enforcement discretion took effect in 2013, patients with Crohn's disease (CD) and ulcerative colitis (UC) have enrolled in multiple trials as they are at an increased risk of Clostridium difficile infection. Trials of FMT to treat the inflammatory bowel disease (IBD) directly, independent of the impact on Clostridium difficile infection, are of particular interest to patients. Aim: We aimed to summarize the completed, ongoing and future FMT trials to explore where evidence is being generated for CD and UC treatment algorithms. Methods: We searched PubMed for randomized trials related to FMT resulting in 930 citations. ClinicalTrials.gov and the WHO Trial Registry yielded an additional 257 and 262 studies. Trial registrations, published randomized trials and systematic reviews were reviewed to identify randomized trials of FMT with an IBD indication. Results: Four randomized trials were identified in the published literature (277 UC participants). An additional 33 randomized trials were identified from the trial registries. Most trials were for UC (70%), followed by 18% for CD and 12% allowing both conditions. The majority of studies were for induction of remission (97%) with the Mayo score and HBI as the most common inclusion criteria. There are 21 ongoing trials (5 CD, 14 UC, 2 both) scheduled to end between 2017 and 2023, and 5 trials that have not yet started to recruit participants (0 CD, 4 UC, 1 for both). Conclusions: As more evidence is published in peer reviewed journals, the IBD community will be able to make an evidence-based decision on the role of FMT to induce remission in UC. Evidence is lacking on UC maintenance of remission and the role of FMT for CD.